2019
DOI: 10.1136/bmjqs-2018-008975
|View full text |Cite
|
Sign up to set email alerts
|

Patient activation intervention to facilitate participation in recovery after total knee replacement (MIME): a cluster randomised cross-over trial

Abstract: BackgroundPatient participation in care is a fundamental element of safe and high-quality healthcare with the potential to enhance health outcomes and improve patient satisfaction.ObjectivesTo test the efficacy of a clinician-facilitated, bedside multimedia (MyStay) intervention designed to support patient participation in their recovery after total knee replacement surgery. The primary outcome was patients’ reported worst pain intensity on postoperative day 3. Secondary outcomes were patient activation, lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…One indirect measure of patient participation in care and recovery is improvements in clinical outcomes and acute care length of stay . In one study of an e‐health platform intervention by Cook et al, patients whose self‐reported mobility scale scores were higher also had a shorter length of stay in hospital compared to standard practice (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…One indirect measure of patient participation in care and recovery is improvements in clinical outcomes and acute care length of stay . In one study of an e‐health platform intervention by Cook et al, patients whose self‐reported mobility scale scores were higher also had a shorter length of stay in hospital compared to standard practice (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…[39][40][41] One system described using interactive music therapy, 42 two other described a Web-based virtual nurse designed for patient-provider communication and patient education, 42,43 and one described a bedside educational multimedia program intervention accessed through iPads. 44 Finally, one paper described a personalized patient-controlled analgesia (PCA) device for oral medications. 45…”
Section: Standalone Interactive Systemsmentioning
confidence: 99%
“…Two studies investigated the development of a virtual nursing Web-based intervention to improve pain relief in cardiac surgery patients and reported on the preliminary effects of the system. 42,44 The Web application generates reflective personalized activities and specific educational messages designed for patients based on their beliefs and attitudes. The system messages are transmitted through videos of a virtual nurse, animations, stories, and texts.…”
Section: Interactive Musicmentioning
confidence: 99%
See 2 more Smart Citations